Genome-Wide Approaches to Unravel the Host Factors Involved in Chikungunya Virus Replication - Tanaka, Atsushi; Suzuki, Youichi (Frontiers in Microbiology, 2022)
Chikungunya virus (CHIKV), the causative agent of Chikungunya fever (CHIKVF) that is often characterized by fever, headache, rash, and arthralgia, is transmitted to humans by Aedes mosquito bites. Although the mortality rate associated with CHIKV infection is not very high, CHIKVF has been confirmed in more than 40 countries, not only in tropical but also in temperate areas. Therefore, CHIKV is a growing major threat to the public health of the world. However, a specific drug is not available for CHIKV infection. As demonstrated by many studies, the processes completing the replication of CHIKV are assisted by many host factors, whereas it has become clear that the host cell possesses some factors limiting the virus replication. This evidence will provide us with an important clue for the development of pharmacological treatment against CHIKVF. In this review, we briefly summarize cellular molecules participating in the CHIKV infection, particularly focusing on introducing recent genome-wide screen studies that enabled illuminating the virus-host interactions.